2012
DOI: 10.1371/journal.pone.0048925
|View full text |Cite
|
Sign up to set email alerts
|

Pgc-1α Overexpression Downregulates Pitx3 and Increases Susceptibility to MPTP Toxicity Associated with Decreased Bdnf

Abstract: Multiple mechanisms likely contribute to neuronal death in Parkinson’s disease (PD), including mitochondrial dysfunction and oxidative stress. Peroxisome proliferator-activated receptor gamma co-activator-1 alpha (PGC-1α) positively regulates the expression of genes required for mitochondrial biogenesis and the cell’s antioxidant responses. Also, expression of PGC-1α-regulated genes is low in substantia nigra (SN) neurons in early PD. Thus upregulation of PGC-1α is a candidate neuroprotective strategy in PD. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 70 publications
3
51
0
1
Order By: Relevance
“…Our finding of increased expression of PGC-1a, a well-known master regulator of mitochondrial biogenesis, previously demonstrated to regulate mitochondrial density in neurons [34,35], is also compatible with the hypothesis of increased mitochondrial biogenesis in SNc compared to VTA DA neurons. Much recent work has explored the involvement of PGC-1a in neurodegenerative diseases [36,37], although the results of experiments evaluating the effects of overexpressing PGC-1a on the vulnerability of mouse DA have been controversial [34,[38][39][40]. This may result from the difficulty to increase OXPHOS and ATP production without increasing oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of increased expression of PGC-1a, a well-known master regulator of mitochondrial biogenesis, previously demonstrated to regulate mitochondrial density in neurons [34,35], is also compatible with the hypothesis of increased mitochondrial biogenesis in SNc compared to VTA DA neurons. Much recent work has explored the involvement of PGC-1a in neurodegenerative diseases [36,37], although the results of experiments evaluating the effects of overexpressing PGC-1a on the vulnerability of mouse DA have been controversial [34,[38][39][40]. This may result from the difficulty to increase OXPHOS and ATP production without increasing oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Compatible with this conclusion, we found that increasing OXPHOS with AICAR, a well-known activator of AMPK [41,42], failed to decrease the vulnerability of SNc DA neurons ( Figure S7). Although we found that AICAR caused a marked increase in OXPHOS that is likely to result from an increase in mitochondrial biogenesis [42], this increased mitochondrial function did not result in reduced vulnerability against MPP + or rotenone ( Figure S7), arguing that an increase in basal OXPHOS is not an ideal strategy to promote neuroprotection in SNc DA neurons, a conclusion that is compatible with previous results [34,40].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, sustained high overexpression of PGC-1α produced toxic effects in muscles and heart, caused or accompanied by extensive mitochondrial proliferation and by myopathy (28,29). Extremely high levels of PGC-1α achieved with adenoviral vectors also resulted in deleterious effects in dopaminergic neurons, in susbtantia nigra (30,31) as opposed to the striatum, where fourfold higher levels were not toxic, in mouse models of Huntington's and Parkinson's diseases (32,33). The different outcomes in different studies must relate to the fact that dopaminergic neurons are more susceptible to degeneration from oxidative damage than other neuronal subtypes and suggest that selective delivery in specific brain regions is necessary to achieve beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the transgenic overexpression of PGC-1α was proved to protective against MPTP (Mudo et al, 2012), on the other hand, the adenovirus vector-mediated overexpression of PGC-1α resulted in dopamine depletion in the SN (Ciron et al, 2012) and consequently enhanced susceptibility to MPTP (Clark et al, 2012). The clarification of this issue needs further studies.…”
mentioning
confidence: 96%